An overview of fault zone permeabilities and groundwater level steps in the Roer Valley Rift System. (2019) - Lapperre, Rimbaud E.; Kasse, Cornelis; Bense, Victor F.; Woolderink, Hessel A.G.; Van Balen, Ronald T.
Abstract: Faults in the Roer Valley Rift System (RVRS) act as barriers to horizontal groundwater flow. This causes steep cross-fault groundwater level steps (hydraulic head differences). An overview of the size and distribution of fault-related groundwater level steps and associated fault zone permeabilities is thus far lacking. Such an overview would provide useful insights for nature restoration projects in areas with shallow groundwater levels ( wijstgronden ) on the foot wall of fault zones. In this review study, data on fault zone permeabilities and cross-fault hydraulic head differences were compiled from 39 sources of information, consisting of literature (starting from 1948), internal reports (e.g. from research institutes and drinking water companies), groundwater models, a geological database and new fieldwork. The data are unevenly distributed across the RVRS. Three-quarters of the data sources are related to the Peel Boundary Fault zone (PBFZ). This bias is probably caused by the visibility of fault scarps and fault-adjacent wet areas for the PBFZ, with the characteristic iron-rich groundwater seepage. Most data demonstrate a cross-fault phreatic groundwater level step of 1.0 to 2.5 m. Data for the Feldbiss Fault zone (FFZ) show phreatic cross-fault hydraulic head differences of 1.0 to 2.0 m. In situ measured hydraulic conductivity data (K) are scarce. Values vary over three orders of magnitude, from 0.013 to 22.1 m d −1, are non-directional and do not take into account heterogeneity caused by fault zones. The hydraulic conductivity (and hydraulic resistance) values used in three different groundwater models are obtained by calibration using field measurements. They also cover a large range, from 0.001 to 32 m d −1 and from 5 to 100, 000 days. Heterogeneity is also not taken into account in these models. The overview only revealed locations with a clear cross-fault groundwater level step, and at many locations the faults are visible on aerial photographs as cropmarks or as soil moisture contrasts at the surface. Therefore, it seems likely that all faults have a reduced permeability, which determines the size of the groundwater level steps. In addition, our results show that cross-fault hydraulic head gradients also correlate with topographic, fault-induced offsets, for both the Peel Boundary and the Feldbiss fault zone.